Strategies for failure prevention in a gas motor of launch vehicle control actuation system. (4th February 2020) - Murugesan, V.; Sreejith, P.S.; Sajiv, V.; Anilkumar, A.K.
Hydraulic servo actuators are employed for the thrust vector control of the liquid engines. Vane type gas motor, the prime mover of the system, is a critical subsystem with intricate dynamic elements such as rotor, bearings, vanes and speed regulator. Failure prevention of such critical systems, which is of paramount importance to the success of a launch vehicle mission, depends on making the design robust and ensuring that the critical parameters of the system hardware are within the specified range to give optimal performance. This paper addresses the strategies for achieving the design robustness through severe environmental stress testing and realisation of system hardware complying with quality requirements, which are essential for failure prevention. Towards this, critical environments for the gas motor have been identified and testing extended much beyond the system qualification levels, inducing failures. The test observations and data are analysed critically and design modifications made for broadening the operating environments. The quality systems and procedures for the system hardware are strengthened to assure reliable performance of the gas motor.